PESQUISAS COLABORATIVAS INTERNACIONAIS NO CAMPO DA PSICOLOGIA DA MÚSICA: UM RELATO DE EXPERIÊNCIAS (Orfeu, 2019)
Internationalization actions have been increasingly encouraged under the Graduate Programs in Brazil. This article focuses on the presentation of two international researches, carried out collaboratively between researchers from the University of Bologna (Italy) and the Federal University of Paraná (Brazil). The studies presented were conducted through a study on Social Representations, based on Social Psychology, and a study based on Cognitive Psychology / Psychology, focusing on Creativity and Flow Theory. Both investigations brought relevant consequences for the UFPR Graduate Program in Music, generating collaborative publications and developments in subsequent studies that expanded the investigative possibilities for the Cognition / Music Education research line.
Keywords: Internationalization; Music research; Social Representations; MIROR Project